2018
DOI: 10.1080/10408398.2018.1474170
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities, biosynthesis and biotechnological production of phenolic acids in Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza (Danshen in Chinese), is a well-known traditional Chinese medicinal plant, which is used as not only human medicine but also health-promotion food. Danshen has been extensively used for the treatment of various cardiovascular and cerebrovascular diseases. As a major group of bioactive constituents from S. miltiorrhiza, water-soluble phenolic acids such as salvianolic acid B possessed good bioactivities including antioxidant, anti-inflammatory, anti-cancer and other health-promoting activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(133 citation statements)
references
References 92 publications
1
122
0
Order By: Relevance
“…Tanshinone is a natural terpenoid and the main bioactive component isolated from traditional Chinese medicine Salvia miltiorrhiza. It is traditionally used in the treatment of cardiovascular and cerebrovascular diseases in China Shi et al, 2019;Sun et al, 2019). Modern pharmaceutical studies showed that tanshinone also possess antiangiogenic, antioxidant, antibacterial, anti-inflammatory, and antitumor activities (Wang et al, 2016;Gao et al, 2017;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tanshinone is a natural terpenoid and the main bioactive component isolated from traditional Chinese medicine Salvia miltiorrhiza. It is traditionally used in the treatment of cardiovascular and cerebrovascular diseases in China Shi et al, 2019;Sun et al, 2019). Modern pharmaceutical studies showed that tanshinone also possess antiangiogenic, antioxidant, antibacterial, anti-inflammatory, and antitumor activities (Wang et al, 2016;Gao et al, 2017;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous MeJA treatment significantly promotes salvianolic acid accumulation in S. miltiorrhiza hairy roots In recent years, salvianolic acid compounds have found widespread use as treatments for coronary heart disease and angina pectoris. Among these compounds, RA and SAB have high economic value and medicinal efficacy (Shi et al 2019). Therefore, studying the molecular mechanism of salvianolic acid biosynthesis could facilitate efforts to promote the accumulation of salvianolic acids in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on several studies, PAL is known as a critical enzyme in the production of many phenolic compounds such as flavonoids, lignans, coumarins and phenolic acids (Xu et al 2016, Nourozi et al 2019. Some reports have also confirmed that PAL is a committed-step enzyme responsible for RA biosynthesis (Nourozi et al 2019, Shi et al 2019. Results disclosed that SNPs-induced PAL activity that catalyzes the conversion of phenylalanine to the precursors of phenolic compounds.…”
Section: Effects Of Snps On Defense Phenylpropanoids/phenolic Compoundsmentioning
confidence: 98%